Response of chromoblastomycosis to voriconazole - Alexandre Moretti de Lima; Gabriely Lessa Sacht; Lauren Zogbi Pereira de Paula; Gabriela Kimie Aseka; Hermann Soares Goetz; Maicon Felippe Gheller; Pedro de Freitas Silva Torraca (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Chromoblastomycosis is a chronic fungal infection of the epidermis, dermis and subcutaneous tissue, in which the most common etiologic agent in Brazil is Fonsecaea pedrosoi. In more advanced cases we found many difficulties in their treatment, and therefore, we report a case of extensive and severe chromoblastomycosis, with therapeutical failure of first choice treatments, but good response to voriconazole.